Le calendrier révolutionnaire de 1793 ou les quatre saisons de la République - Matyaszewski, Paweł (Studia Romanica Posnaniensia, 2021)
The authors of the revolutionary calendar, in particular Gilbert Romme and Fabre d’Églantine not only want to put the past behind by implicating a new time and new order but also try to prove the relation between history and nature using the example of the events of the Revolution and their compliance with the laws of the universe. They introduce an innovative nomenclature in order to specify the names of particular days and months but they do not change the natural four-season model of division. The goal of the presented idea is to enrich the natural cycle with a new content expressing the spirit and the objectives of the Republic while following the laws of nature.